Ukraine: From Chernobyl’ to Sovereignty
XXVI, 174 p.
Keywords: A collection of interviews that reflects the changing face of the Ukraine, the second largest Soviet republic. The interviews demonstrate the transformation the Ukraine has gone through since the early stages of perestroika.